Repeated long-term cover cropping and nitrogen fertilization enhance soil multifunctionality - Lin Li; Wanyu He; Qilong Du; Xue Zhao; Minghui Meng; Guangjin Wu; Guangxi Liu; Simeng Wang; Jun Wang; Fazhu Zhao; Jieying Wang (Agriculture, Ecosystems & Environment, 2026)

Adaptive laboratory evolution of Lactiplantibacillus plantarum for enhanced lactose metabolism: Phenotypic changes and underlying molecular mechanisms - Hong Li; Simeng Wang; Jiao Wu; Xingyu Li; Ruihang Liu; Yuenan Wang; Tong Dan (Food Research International, 2026)

Probiotics and Bacteriocins Against SARS-CoV-2: Therapeutic Frontiers and Mechanistic Insights - Simeng Sun; Xinyue Guo; Simeng Liu; Shuhong Wu; Lei Ma; Hongru Yang (Probiotics and Antimicrobial Proteins, 2026)

Warming attenuates root-induced decomposition enhancement via soil moisture limitation in a subtropical forest of China - Shuai Liu; Simeng Wang; Yuxiang Xu; Xiangliang Li; Qianqian Xi; Chuansheng Wu (Acta Oecologica, 2026)

Disrupting KRAS–AGO2 interaction: a dual-pronged strategy to sensitize chemo-immunotherapy in KRAS-mutated colorectal cancer - Jingyi Xie; Simeng Wang; Juan Liu; Yan Zhang; Haixiao Zhu; Rongrong Cui; Yao Yao; Wei Yu; Peng Hou (Apoptosis, 2026)

The mixed cover crops and nitrogen fertilization decrease the soil microbial dormancy - Simeng Wang; Xue Zhao; Wanyu He; Jieying Wang; Minghui Meng; Xiya Xiong; Min Xie; Guangjin Wu; Qilong Du; Lin Li; Guangxi Liu; Jun Wang; et al. (Plant and Soil, 2026)

Projection of distribution shift for Pacific saury (Cololabis saira) in the Northwestern Pacific Ocean under climate change - Zi Yang; Simeng Li; Xiaoxue Liu; Libin Dai; Jie Cao; Siquan Tian (Regional Studies in Marine Science, 2026)

Metagenomic analysis of lactic acid bacteria communities in inner Mongolian fermented dairy products: influence of milk source and geography - Hong Li; Haimin Hu; Wenhui Lu; Jinhui Liu; Qingting Peng; Simeng Wang; Tong Dan (Food Research International, 2026)

An efficient embryogenic cell suspension enabling somatic embryogenesis in Phyllostachys edulis - Simeng Kong; Huan Liu; Kaiting Wang; Xiaohong Zhou; Xinyi Yang; Juan Zhuo; Xiangyu Li; Xinchun Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Comparative genomics reveals population structure and ecological adaptation in Lactobacillus helveticus - Haimin Hu; Jiao Wu; Jiaqi Sun; Simeng Wang; Jinhui Liu; Tong Dan (Food Research International, 2026)

Genome-wide identification of oat EIL gene family and analysis of expression patterns under abiotic stress - Xiaodong Guo; Xuanyu Liu; Jiaming Nie; Qidi Zhang; Simeng Cai; Huiyan Liu; Bing Han; Hongbin Zhao (Genetic Resources and Crop Evolution, 2026)

Drug repurposing: a promising drug discovery strategy for the treatment of emerging epidemic infectious disease - Simeng Zhang; Ruiqing Zhang; Lidan Zheng; Yang Liu; Qing Fan; Yingxu Liu; Xiangzhen Ning; Yanmin Zhang; Yadong Chen; Haichun Liu (Molecular Diversity, 2026)

Long-term scenarios for climate adaptation of cotton crops in China, considering multidimensional biophysical and socio-economic scenario analysis - Simeng Guo; Fengqi Wu; Yuhan Wang; Jian Wang; Zhenggui Zhang; Zhanlei Pan; Chenxi Chong; Pengcheng Li; Weibin Huang; Guilan Sun; Xin Li; Shuchen Wang; et al. (Journal of Cleaner Production, 2026)

Response of organic matter decomposition and nitrogen transformation in surface sediment to Hyriopsis cumingii bioturbation - Zhaoxing Wu; Zhaohui Tian; Junfeng Ma; Simeng Chen; Shaogang Xu; Hongda Liu; Yan Chen (Journal of Cleaner Production, 2026)

Feasibility of planting shrubs in arid areas from a water balance perspective - Chenguang Zhao; Chao Guan; Tengfei Yu; Jiazheng Wang; Huiying Li; Xia Wang; Baojun Zhang; Simeng Kou; Xuejuan Liu; Changming Zhao (Journal of Hydrology, 2025)

Therapeutic strategy for corneal edema: Nicotinamide - based anterior chamber perfusion agent for efficacy - verified treatment - Liwei Huang; Xiaomin Liu; Xiaoming Wu; Haoyun Duan; Simeng Zheng; Xiangyue Hu; Shengqian Dou; Xiaoyu Li; Zongyi Li; Qingjun Zhou; Lixin Xie (Chemical Engineering Journal, 2025)

Naphthenic acids (NAs) - tolerant aerobic granular sludge: Removal performance, degradation mechanism, and microbial response - Jin Li; Shasha Liu; Simeng Li; Jiayu Song; Qinghong Wang; Chunmao Chen (Journal of Environmental Management, 2025)

A transcriptomics-based analysis provides insights into the sex-dependent reproductive toxicity of DEHP in zebrafish (Danio rerio) - Shirui Liu; Simeng Yu; Yankun Huang; Jingyun Zhang; Kai Song; Shenbao Qu; Cixin Li; Aijiang Yang; Xia Hu (Environmental Toxicology and Pharmacology, 2025)

A computational framework for site-city interaction analysis considering seismic wave propagation effects and its application to Beijing CBD - Yuan Tian; Simeng Liu; Siying Chen; Zhen Xu (Soil Dynamics and Earthquake Engineering, 2025)

Novel quantitative method of reactive losses of ambient VOCs coupling chemical transport model simulation with receptor measurement - Yao Gu; Baoshuang Liu; Simeng Ma; Zhongwei Luo; Jinqiu Zhang; Danni Liang; Yafei Li; Yufen Zhang; Yinchang Feng (Journal of Hazardous Materials, 2025)

Carbon, nitrogen, and phosphorus ecological stoichiometry in Cenchrus fungigraminus and soil under waterlogging stress - Simeng Song; Hengyu Zhou; Pingxuan Li; Lin Zhang; Dewei Su; Dan Zheng; Zhaoxiong Zhang; Zongzhi Luo; Shikui Yu; Bin Liu; Zhanxi Lin; Dongmei Lin (Plant and Soil, 2025)

Nuclear protein 1 protects against neonatal hypoxic-ischemic encephalopathy by inhibiting neuronal ferroptosis by improving iron storage - Xining He; Simeng Wei; Yunsheng Fu; Hongxia Li; Jie Zhang; Li Liu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Insight into enhanced catalytic performance of alkali-treated Al2O3 supported Ag catalyst for toluene oxidation - Hongxuan Liu; Xi Chen; Simeng Qiu; Qinhong Wei; Yuan Qin; Lili Ji; Jing Xu (Fuel, 2025)

Comprehensive insights into oil absorption in fried foods: The role of surface characteristics - Shuangyi Zhang; Zhiguo Gong; Simeng Wang; Shuli Zhao; Wei Mao; Bo Liu; Ying Liu (Food Chemistry, 2025)

Ligand exchange by As(V) enhanced desferrioxamine B-induced goethite dissolution: Insights into As mobilization in groundwater systems - Simeng Li; Wei Xiu; Xin Liu; Zhixin Fang; Jonathan R. Lloyd; Huaming Guo (Applied Geochemistry, 2025)

Quantitative source apportionment of surface ozone in Liaoning Province, China, under the Asian summer monsoon background - Ningwei Liu; Simeng Ma; Kun Wang; Sen Yang; Zhigang Zhang (Atmospheric Pollution Research, 2025)

Metabolome genome-wide association analyses identify a splice mutation in AADAT affects lysine degradation in duck skeletal muscle - Dapeng Liu; Wenlei Fan; Youyou Yang; Zhanbao Guo; Yaxi Xu; Jian Hu; Tong Liu; Simeng Yu; He Zhang; Jing Tang; Shuisheng Hou; Zhengkui Zhou (Science China Life Sciences, 2025)

Using explainable machine learning to predict the irritation and corrosivity of chemicals on eyes and skin - Yingxu Liu; Yang Liu; Simeng Zhang; Chen Zeng; Qing Zhang; Yunya Jiang; Xi Yang; Lidan Zheng; Qian Ge; Yanmin Zhang; Yadong Chen; Mengyi Lu; et al. (Toxicology Letters, 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Nomogram for Predicting Long-term Outcomes of Encephaloduroarteriosynangiosis in Toddlers with Moyamoya Disease: a Longitudinal and Cross-sectional Study - Qingbao Guo; Yan-Na Fan; Qian-Nan Wang; Jingjie Li; Cong Han; Zhengxing Zou; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; et al. (Translational Stroke Research, 2025)

Necroptosis in obesity: a complex cell death event - Zunhai Liu; Simeng Wang; Wentao Wang; Rui Lv; Chao Sun (Apoptosis, 2025)

Seasonal variation of underwater sound propagation in the Beibu Gulf - Feihong Zeng; Lingling Xie; Mingming Li; Qiang Li; Simeng Liu (Frontiers in Marine Science, 2025)
Variations in the underwater sound speed significantly influence sound propagation in the ocean, thereby impacting both underwater navigation systems and a substantial portion of marine organisms reliant on sound. This study utilizes cruise data from the Beibu Gulf during the summer and winter of 2023–2024 to explore the seasonal variations in temperature and salinity affecting the sound speed distribution and characteristics of sound propagation. Results indicate significant differences in the sound speed on either side of the 30-m isobath in the Beibu Gulf, with pronounced changes corresponding to seasonal temperature and salinity variations. In summer, the sound speed in the Beibu Gulf exhibits a north-high–south-low pattern. In areas shallower than 30 m, the sonocline is predominantly positive or absent, whereas, in deeper areas, it is mainly negative. During winter, there is a south-high–north-low pattern in sound speed across the Beibu Gulf, with pronounced sound speed extremes in areas shallower than 30 m. Sound propagation simulations based on the Beibu Gulf sound-speed field reveal that sounds at the 100-Hz frequency propagate significantly farther and cover larger areas in depths less than 30 m compared to deeper areas. In summer, this phenomenon is more pronounced than in winter due to the presence of positive sonoclines. The results have significant implications for target detection, underwater acoustic communication, and the protection of aquatic animals that rely on underwater sound for survival in the Beibu Gulf.

Entropy-TOPSIS-based quantitative evaluation of specific roles of the enhanced coagulation process in multi-objective sewage pre-concentration by microfiltration - Yukun Xing; Xiaoxiang Zhang; Simeng Han; Lanxin Ling; Xiyuan Feng; Xiaoyu Zhang; Zhaotong Liu; Zhengyu Jin (Journal of Water Process Engineering, 2025)

Self-Compensating strategy of electronic Structure-Modulated selenide @ carbon nanotube / carbon nanofiber for High-Efficiency electromagnetic wave absorption and corrosion resistance - Simeng Wu; Yanxiang Wang; Jiangyiming Jiang; Yibo Li; Dongming Liu (Chemical Engineering Journal, 2025)

Protein Phosphatase 2ACα Regulates ATR-Mediated Endogenous DNA Damage Response Against Microcephaly - Lin Lin; Jing Ding; Simeng Liu; Chunying Liu; Qing Li; Xiang Gao; Yamei Niu; Wei-Min Tong (Molecular Neurobiology, 2025)

Assessing the impact of various irrigation technologies on agricultural production: A water-energy‑carbon nexus perspective - Sifu Liu; Simeng Cui; Jan F. Adamowski; Nan Wu; Mengyang Wu; Pingping Zhang; Xinchun Cao (Science of The Total Environment, 2024)

Effect of calcium chloride blanching combined with acetic acid soaking pretreatment on oil absorption of fried potato chips - Shuli Zhao; Simeng Wang; Qianru Lu; Ying Liu (Food Chemistry, 2024)

Thioredoxin C of Streptococcus suis serotype 2 contributes to virulence by inducing antioxidative stress and inhibiting autophagy via the MSR1/PI3K-Akt-mTOR pathway in macrophages - Chunxiao Ji; Yanying Pan; Bocheng Liu; Jianying Liu; Chijun Zhao; Zhuyuan Nie; Simeng Liao; Guangwei Kuang; Xin Wu; Quan Liu; Jie Ning; Yulong Tang; et al. (Veterinary Microbiology, 2024)

Exploring emission spatiotemporal pattern and potential reduction capacity in China's aviation sector: Flight trajectory optimization perspective - Simeng Ma; Xuan Wang; Bo Han; Jingbo Zhao; Zhongyi Guan; Jinlong Wang; Yufen Zhang; Baoshuang Liu; Jian Yu; Yinchang Feng; Philip K. Hopke (Science of The Total Environment, 2024)

High-efficiency electro-Fenton synergistic electrocoagulation for enhanced removal of refractory organic pollutants - Kang Liu; Tao Xu; Simeng Hu; Xiaojie Zhuang; Yihui Zhou; Xiping Lei; Xueyuan Zhang; Lianwu Xie (Journal of Environmental Management, 2024)

Climate warming and nitrogen deposition had no significant interaction effect on litter decomposition of subtropical mountain forest in Southwest China - Yue Li; Simeng Wang; Ying Wang; Menglong Bu; Shuai Liu; Chuansheng Wu (Plant and Soil, 2024)

Highly selective oxidation of 3,7-dichloro-8-dichloro methyl quinoline toward quinclorac by CoPc-Mn-Br catalytic system - Simeng Zhu; Peng Liu; Xinlin Hong (Fuel, 2024)

One-step rapid removal of Cu(II) complexes via dual-active-site MOF catalysis with Peroxymonosulfate: Cooperative oxidation and adsorption - Shuo Wang; Simeng Guo; Xuedong Du; Ziqian Liu; Yujia Yang; Yaran Song; Qingrui Zhang (Chemical Engineering Journal, 2024)

Thyroglobulin as a Sensitive Biomarker of Iodine Status in Mildly and Moderately Iodine-Deficient Pregnant Women - Yujie Jiang; Simeng Gu; Zhe Mo; Xueqing Li; Chenyang Liu; Yahui Li; Guangming Mao; Yuanyang Wang; Fanjia Guo; Xiaoming Lou; Xiaofeng Wang (Biological Trace Element Research, 2024)
Pregnant women are more susceptible to iodine deficiency. However, there are limitations in existing indicators for the evaluation of iodine nutrition in pregnant women. The study aimed to explore whether thyroglobulin (Tg) can be used as a more sensitive biomarker for pregnant women with mild and moderate iodine deficiency. A repeated-measure study was conducted among 1332 pregnant women in Zhejiang Province, China. Serum and urine specimens were collected at a mean of 10, 17, and 32 weeks of pregnancy, respectively; thyroid-stimulating hormone (TSH), Tg, and urinary iodine concentrations were measured. Linear mixed effects models were used to determine the associations between interaction of iodine concentrations and increasing gestation week and TSH and Tg, where participants were divided by urinary iodine concentration (UIC). The median Tg concentration was 11.56, 11.45, and 12.43 μg/L in the first, second, and third trimesters, respectively. After controlling the covariates, the interaction effects between the iodine status and gestation week were significant for both TSH and Tg ( p = 0.038 and p = 0.007, respectively). TSH increased with the week of gestation in both iodine concentration groups. Tg increased with advancing pregnancy in the iodine-deficient group whereas it did not in the iodine-sufficient group. There was no significant variation in TSH at each trimester, and Tg was higher in the iodine-deficient group than in the iodine-sufficient group. Tg may be a more sensitive iodine status biomarker than TSH for pregnant women with mild-to-moderate iodine insufficiency.

Risk Factors for Preoperative Cerebral Infarction in Infants with Moyamoya Disease - Qingbao Guo; Songtao Pei; Qian-Nan Wang; Jingjie Li; Cong Han; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; Zhengxing Zou; et al. (Translational Stroke Research, 2024)

Multi-model predictive control strategy for path-following of unmanned surface vehicles in wide-range speed variations - Yingkai Ma; Zhilin Liu; Ting Wang; Simeng Song; Jing Xiang; Xiaoyue Zhang (Ocean Engineering, 2024)

Design and implementation of control system for electroplating wastewater treatment by photovoltaic energy sinusoidal alternating current coagulation technology - Xiting Tang; Tao Xu; Simeng Hu; Kang Liu; Zhen Zeng; Qingyu Wu; Yihui Zhou; Miao He; Xing Cao; Gang Yu (Process Safety and Environmental Protection, 2024)

Intelligence detection of oil absorption in French fries by surface profiles - Simeng Wang; Shuli Zhao; Nan Wang; Qianru Lu; Haile Zhao; Ying Liu; Jinwei Li; Liuping Fan (Food Research International, 2024)

Zinc Oxide Nanoparticles Induce Renal Injury by Initiating Oxidative Stress, Mitochondrial Damage and Apoptosis in Renal Tubular Epithelial Cells - Shuang Liu; Han Zhou; Yang Shi; Simeng Yi; Xinyu Wang; Jingyan Li; Bin Liao; Jimin Cao; Guang Li (Biological Trace Element Research, 2024)

Influence of tall buildings on city-scale seismic response analysis: A case study of Shanghai CBD - Yuan Tian; Siying Chen; Simeng Liu; Xinzheng Lu (Soil Dynamics and Earthquake Engineering, 2023)

EMPMR berthing scheme: A novel event-triggered motion planning and motion replanning scheme for unmanned surface vessels - Shouzheng Yuan; Zhilin Liu; Yuxin Sun; Simeng Song; Zhongxin Wang; Linhe Zheng (Ocean Engineering, 2023)

Nitrogen stress alters trade-off strategies between reproduction and vegetative growth in soybean - Menglong Bu; Yue Li; Simeng Wang; Changjiang Huang; Chuansheng Wu; Shuai Liu (Brazilian Journal of Botany, 2023)

Insight into influence of process parameters on co-pyrolysis interaction between Yulin coal and waste tire via rapid infrared heating - Yuxin Wen; Simeng Liu; Shihao Fu; Zhiheng Wang; Haoquan Hu; Lijun Jin (Fuel, 2023)

Changes in within-boll yield components explain cotton yield and quality variation across planting dates under a double cropping system of cotton-wheat - Simeng Guo; Taijie Liu; Yingchun Han; Guoping Wang; Wenli Du; Fengqi Wu; Yabing Li; Lu Feng (Field Crops Research, 2023)

Heme oxygenase-1 protects against endotoxin-induced acute lung injury depends on NAD+-mediated mitonuclear communication through PGC1α/PPARγ signaling pathway - Simeng He; Jia Shi; Wenming Liu; Shihan Du; Yuan Zhang; Lirong Gong; Shuan Dong; Xiangyun Li; Qiaoying Gao; Jing Yang; Jianbo Yu (Inflammation Research, 2022)

ALOS-Based USV Path-Following Control with Obstacle Avoidance Strategy - Zhilin Liu; Simeng Song; Shouzheng Yuan; Yingkai Ma; Zongxun Yao (Journal of Marine Science and Engineering, 2022)
Path following and obstacle avoidances are used in heading control and path replanning for unmanned surface vessels (USVs), which have attracted the interest of many researchers over the years. This paper investigates the path-following and obstacle avoidance problems for USVs. First, on the basis of the current position and desired path, an adaptive line-of-sight (ALOS) algorithm is used to obtain the desired heading angle, and the sideslip angle compensation is considered. Then, to ensure that the USV follows the desired path. Model predictive control (MPC) is used to reduce the lateral error. The event-triggered mechanism (ETM) strategy is utilized to reduce the computational cost of MPC. Moreover, to obtain accurate state quantities in real time, a linear extended state observer (LESO) is used to counteract the effects of external disturbances and the nonlinear term of the model. Furthermore, an improved obstacle avoidance algorithm based on the geometric relationship is proposed. This method can better ensure USV navigation safety and reduce consumption and computation. Lastly, multiple simulation experiments illustrate that the algorithm improves the path-following capability and security and ensures smooth input changes by setting input constraints. Therefore, the designed controller has better feasibility and robustness.

NEK7: a new target for the treatment of multiple tumors and chronic inflammatory diseases - Jin Wang; Simeng Chen; Min Liu; Min Zhang; Xiaoyi Jia (Inflammopharmacology, 2022)

Endophytic bacterial community diversity in two citrus cultivars with different citrus canker disease resistance - Bing Liu; Jiahao Lai; Simeng Wu; Junxi Jiang; Weigang Kuang (Archives of Microbiology, 2021)

Antibacterial activity of ruthenium polypyridyl complexes against Staphylococcus aureus and biofilms - Simeng Bu; Guijuan Jiang; Guangbin Jiang; Jinyao Liu; Xiaoli Lin; Jihong Shen; Yanshi Xiong; Xuemin Duan; Jintao Wang; Xiangwen Liao (JBIC Journal of Biological Inorganic Chemistry, 2020)

P53/PUMA are potential targets that mediate the protection of brain-derived neurotrophic factor (BDNF)/TrkB from etoposide-induced cell death in neuroblastoma (NB) - Zhongyan Hua; Yue Zhan; Simeng Zhang; Yudi Dong; Min Jiang; Fei Tan; Zhihui Liu; Carol J. Thiele; Zhijie Li (Apoptosis, 2018)

FRZB1 rs2242070 polymorphisms is associated with brick tea type skeletal fluorosis in Kazakhs, but not in Tibetans, China - Yanmei Yang; Qiaoshi Zhao; Yang Liu; Xiaona Liu; Yanru Chu; Huazhu Yan; Yumei Fan; Simeng Huo; Limei Wang; Qun Lou; Ning Guo; Dianjun Sun; et al. (Archives of Toxicology, 2018)

Cry1Ab Adsorption and Transport in Humic Acid-Coated Geological Formation of Alumino-Silica Clays - Hongying Yuan; Simeng Li; Junliang Liu; Chengyi Song; Gang Chen (Water, Air, & Soil Pollution, 2017)

Erratum to: The role of particle size of glyburide crystals in improving its oral absorption - Wenqian Yang; Yongjun Wang; Qiang Fu; Zhibin Guo; Bingjun Sun; Wen Liu; Yaxuan Liu; Simeng Mu; Mengran Guo; Jingru Li; Xiaohui Pu; Zhonggui He (Drug Delivery and Translational Research, 2017)

The role of particle size of glyburide crystals in improving its oral absorption - Yongjun Wang; Wenqian Yang; Qiang Fu; Zhibin Guo; Bingjun Sun; Wen Liu; Yaxuan Liu; Simeng Mu; Mengran Guo; Jingru Li; Xiaohui Pu; Zhonggui He (Drug Delivery and Translational Research, 2017)

NKCC1 up-regulation contributes to early post-traumatic seizures and increased post-traumatic seizure susceptibility - Fushun Wang; Xiaowei Wang; Lee A. Shapiro; Maria L. Cotrina; Weimin Liu; Ernest W. Wang; Simeng Gu; Wei Wang; Xiaosheng He; Maiken Nedergaard; Jason H. Huang (Brain Structure and Function, 2017)